Pelatihan Penanganan Ikan Tuna Sirip Kuning (Thunnus albacares) Dengan Es Batu Secara Bulking Di PPI Hamadi Kota Jayapura - Willem Siegers Siegers; Ade Kurniawan; Dahlan Dahlan; Yudi Prayitno; Sitti Khairul Bariyyah; Ralph.A.N. Tuhumury; Imran Syafei M. Nur (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The aims of this service is to increase the knowledge and skills of fish traders in handling yellowfin tuna by bulking using crushed ice cubes without mixing with water in the box and controlling the quality of fish using an organoleptic table score sheet during cooling process for three days. The method used is the early preparation of the training by conducting a pretest, delivering material and discussion, observing the quality assessment of fish by describing the changes that occur during storage with an explanation of the application theory as well as the implementation of practicum, interviews and evaluation of the final results of the activity by conducting a post-test. The results of the community service implementation attended by 15 participants from fish traders, about 48% was good in understanding and mastering the knowledge of refrigeration fish, about 28% was sufficient in accepting the knowledge and 24% was lacking in understanding the knowledge of refrigeration fish. The average value after given the training is 64.1.